Robust Superhydrophobic Fabric Bag Filled with Polyurethane Sponges Used for Vacuum‐Assisted Continuous and Ultrafast Absorption and Collection of Oils from Water. Issue 9 (10th February 2016) - Li, Jian; Yan, Long; Tang, Xiaohua; Feng, Hua; Hu, Dongcheng; Zha, Fei
Abstract : Removal of oil from water has become an increasingly important field due to the frequent oil spill accidents as well as industrial oily wastewater. In this study, a bag is made from superhydrophobic fabric and stuffed with pristine polyurethane (PU) sponge just utilizing the synergetic effect of the superhydrophobic and superoleophilic selective absorption of oil from water of the fabric and the excellent large volume‐based oil storage capacity of the PU sponge. The superhydrophobic filling bag can quickly absorb and collect a large amount of oil from a polluted water surface with the separation efficiency always above 98.2% for a series of oil/water mixtures. In addition, the filled orignial sponges exhibit large volume‐based absorption capacity up to 20–36 times its own weight, keeping nearly the same absorption capacity with the previous reported hydrophobic modified sponges. Furthermore, the superhydrophobic bag filled with PU sponges can continuously and efficiently absorb oils from water surfaces with high‐speed, removing about 40 L of kerosene in 150 min under a continuous vacuum regime. Moreover, the as‐prepared superhydrophobic filling bag also shows high selectivity and excellent oil storage stability; and no oil escapes from the bag even under harsh conditions, including strong acidic, alkaline, salt aqueous solutions, hot water, and mechanical abrasion. Abstract : A superhydrophobic fabric bag is stuffed with pristine polyurethane (PU) sponge to utilize the synergetic effect of superhydrophobic and superoleophilic selective absorption of the fabric and the excellent large volume‐based oil storage capacity of the PU sponge. When connected with a vacuum system, the superhydrophobic filling bag can continuously and efficiently absorb oils from water surfaces with high‐speed.